2008
DOI: 10.1182/blood-2008-05-157529
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer T-cell autoreactivity leads to a specialized activation state

Abstract: Natural killer T (NKT) cells are innate-likeT cells that recognize specific microbial antigens and also display autoreactivity to self-antigens. The nature of NKT-cell autoreactive activation remains poorly understood. We show here that the mitogenactivated protein kinase (MAPK) pathway is operative during human NKT-cell autoreactive activation, but calcium signaling is severely impaired. This results in a response that is biased toward granulocyte macrophage colony-stimulating factor (GM-CSF) secretion becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 51 publications
8
58
1
Order By: Relevance
“…The lower-well cells were then harvested for use in the analyses described below. Because we have found that human NKT cells that are activated by recognition of auto-antigens mainly secrete GM-CSF and IL-13, whereas those that are stimulated by ␣-GalCer also secrete other cytokines (such as IFN-␥ and IL-4) that may influence monocyte differentiation [49], we compared NKT-instructed APCs in which the NKT cells were stimulated by untreated monocytes (i.e., presenting auto-antigen), with those that differentiated in response to NKT cells that were stimulated by ␣-GalCer pulsed monocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower-well cells were then harvested for use in the analyses described below. Because we have found that human NKT cells that are activated by recognition of auto-antigens mainly secrete GM-CSF and IL-13, whereas those that are stimulated by ␣-GalCer also secrete other cytokines (such as IFN-␥ and IL-4) that may influence monocyte differentiation [49], we compared NKT-instructed APCs in which the NKT cells were stimulated by untreated monocytes (i.e., presenting auto-antigen), with those that differentiated in response to NKT cells that were stimulated by ␣-GalCer pulsed monocytes.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously found that NKT cells that are activated by recognition of auto-antigens secrete little or no IFN␥ or IL-4, whereas those that are activated by the potent agonist ␣-GalCer robustly produce these cytokines [43,49]. Since exposure to IFN-␥ has been associated with enhancing IL-12p70 production by myeloid DCs, we investigated whether the route of NKT cell activation influences the pattern of cytokine production by the resulting APCs.…”
Section: Cytokine Production By Nkt-instructed Apcsmentioning
confidence: 98%
“…These effects were observed with two different types of transfectants (THP-1 and C1R), excluding unique behavior associated with the nature of APCs. The differential influence on the type of released cytokines probably reflects the reported different signal strength required for secretion of GM-CSF versus IL-4 and IFN-γ (12). The presence of CD1e might influence the number and nature of CD1-antigen complexes, leading to a reduced TCR signal strength that might affect IFN-γ production more readily than that of GM-CSF.…”
Section: Discussionmentioning
confidence: 99%
“…CD1e might directly influence the number of CD1d-antigen complexes available over time, which has been shown to affect the type of cytokines released (12)(13)(14). To test this possibility, antigen-pulse experiments were performed to compare the time required for the generation of CD1d-antigen stimulatory complexes.…”
Section: Cd1e Effects On Exogenous Glycolipid Antigen Presentation Tomentioning
confidence: 99%
“…iNKT cells contain preformed IFN-g mRNA in their cytoplasm, which promotes immediate secretion of this cytokine on TCR stimulation at levels 200 times higher than conventional MHC-restricted CD4 þ T cells (Stetson et al 2003). This secretion of cytokines is controlled by the strength of TCR signal received during antigen recognition (Wang et al 2008), which depends on the number of CD1 complexes as well as their persistence on the surface of APCs. In addition, human NKT cells express granulysin (Gansert et al 2003) that participates in killing intracellular bacteria resident within target cells.…”
Section: Functions Of Cd1-restricted T Cells During Mycobacterial Infmentioning
confidence: 99%